Electricity Price Forecasting Using Monte Carlo Simulation: The Case of Lithuania - Ngujen Tat, Andrejus (Ekonomika, 2018)
The main purpose of this article is to determine the practical use of the Monte Carlo simulations in electricity markets for forecasting future prices. First, we review the structure of the electricity markets – how they work, what implications do they have and how they’ve evolved during the last decades. Second, we discover that there are only few researches that have been made on this topic as well as there haven’t being made any researches regarding the Lithuanian electricity market. Then, we will carry out an analysis on how to use a Monte Carlo simulation approach in electricity markets. A Mean-Reverting process method will be introduced, which, at first, was used to predict oil prices. Also, we analyze the essence of price spikes and find a solution on how to predict them.